Pengembangan Bahan Ajar PAI SMP NU Palembang Berbasis Kemampuan Otak - Zuhdiyah Zuhdiyah (Intizar, 2018)
Learning is related to students' understanding of the material taught by the teacher so that students get the best results. The problems that exist, the teaching materials of Islamic Education and Character used in NU Middle School have not been compiled based on needs analysis and are not developed based on the rules of developing standardized teaching materials. So that this study aims to produce a model of teaching material for Islamic Education and Character Skills for Class VII Palembang NU Middle School Based on Brain Ability that is valid, practical, and effective. The type of research used is the research and development model Jan Van Den Akker. Results obtained from the study are: (1) RPP based on the results of theoretical studies that are in line with the results of needs analysis; (2) teaching materials for Islamic Education and Character in SKI Material for Class VII Palembang NU Middle School Based on Brain Ability has been proven to be valid, practical and effective. Valid with an average score of 99.09%; practical with perceptual scores in the range 1024 and 1280 (in the category strongly agree); effective with the results of the Paired T test 32,769 with a significance level of 0.00 or 32,769> 0.00 so that it can be concluded that H0 is rejected, therefore Ha is accepted.